COMPOSITION AND CHARACTERISTICS OF BRICK FOR CONSERVATION AND RESTORATION MATERIALS OF HERITAGE BUILDINGS AS AN INSPIRATION FOR SUSTAINABLE CONSTRUCTION: Received: 24th October 2025, Revised: 30th October 2025, 5th November 2025, Accepted: 12th November 2025, Date of Publication: 3rd December 2025 - Hana Wardani Puruhita; Senot Sangadji; Endah Safitri; Stefanus Adi Kristiawan (MATTER: International Journal of Science and Technology, 2025)
To realize sustainable Cultural Heritage buildings and preserve cultural heritage, an appropriate concept of cultural heritage restoration and material appropriate to their function are needed. One of which is brick material for heritage buildings. Current bricks are different from heritage/old bricks, visually evident through their shape and colour. Heritage bricks must be studied to find their characteristics and composition so they can be used as cultural heritage restoration materials in the world. The composition and characteristics of heritage bricks have been studied and the results show that the physical and mechanical properties of heritage bricks vary. Therefore, research is needed on the development of renewable/repair heritage bricks as materials in the restoration of cultural heritage buildings, by identifying the characteristics and composition of renewable bricks. The methods applied include experiments and testing in the field and laboratory. The characteristics of renewable bricks in terms of physical strength have been designed with a size of 5.5x14x25.5 without shrinkage because they come from selected clay, have flat surfaces, sharp corners, and colours similar to heritage bricks. Tests were also conducted on the mechanical properties, such as water absorption, apparent density, and compressive strength, of all heritage bricks, and the best values ​​for use as renewable materials were obtained.